EFFECTIVENESS OF GROUP COUNSELING WITH SELF MANAGEMENT TECHNIQUES TO REDUCE PROCRASTINATION ACADEMICS FOR STUDENTS 2021 FOK PGRI BANYUWANGI UNIVERSITY: EFEKTIFITAS KONSELING KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PROKRASTINASI AKADEMIK PADA MAHASISWA 2021 FOK UNIVERSITAS PGRI BANYUWANGI - ingrid indirasitna; Heribertus Wicaksono; Ratna Wulandari (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
Academic procrastination is a type of procrastination carried out on types of formal tasks related to academic assignments. This research aims to, determine the effectiveness of self-management technique group counseling in reducing the academic procrastination behavior of FOK 2021 University of Banyuwang students. This research uses quantitative methods. This type of research is a quasi-experiment with a nonequlvalent pretest-posttest group design. The research results show that: Tcount on the output shows the number 19.395, this means there is a decline. If t count > t table, then Ho is rejected. Which means 19.395 > 2.015, thus where Ha reads "Self management technique group counseling is effective in reducing academic procrastination behavior of FOK students class of 2021 at PGRI Banyuwangi University". Apart from that, it was found that the average score of the experimental group when conducting the pretest and posttest was greater than that of the control group (20.1 > 4.5). So it can be concluded that group counseling services with self-management techniques can reduce academic procrastination behavior in FOK 2021 Universitas PGRI Banyuwangi students."